An Analysis of Students’ Motivation in Studying English During Covid-19 Pandemic - Putu Subakthiasih; I Gusti Ayu Vina Widiadnya Putri (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study focuses to investigate students’ motivation in studying English during Covid-19 Pandemic, whether they had intrinsic or extrinsic motivation. This research was a survey method and the technique sampling used in this study was random sampling. Furthermore, the instrument used questionnaire to collect the data. The questionnaire consists of 20 questions in which question 1-10 are questions for intrinsic motivation. The question 11-20 are extrinsic motivation. The result of this study shows that the total mean score of intrinsic motivation is higher than the total mean score of extrinsic motivation 4.20 > 3.39. It means that first semester of English students at Faculty of Foreign Language, Mahasaraswati Denpasar University had the higher intrinsic motivation than extrinsic motivation in learning English during Covid-19 Pandemic. In other words, the motivation to learn English that comes from inside students was higher than the motivation comes from outside students. Keywords: Students’ Motivation, Studying English, Covid-19 Pandemic